ANALYSIS OF UMKM FINANCIAL REPORTS BASED ON FINANCIAL ACCOUNTING STANDARDS FOR SMALL AND MEDIUM MICRO ENTITIES (SAK EMKM) (BERKAH RIDHO BUSINESS CASE STUDY) - Yogi Prasetyo; Maralus Samosir; Eduward Tony Sitorus; Ringkot P Nainggolan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to assist in the preparation of financial statements in accordance with SAK EMKM at Usaha Berkah Ridho, located in Milangasri Village, Panekan District, Magetan Regency. Usaha Berkah Ridho is a manufacturing company that produces cakes. This research uses a descriptive approach with quantitative and qualitative methods, as well as data collection techniques such as interviews, documentation, and observation. The results of the research show that Usaha Berkah Ridho has not yet prepared financial statements in accordance with SAK EMKM due to a lack of understanding of these standards. Currently, the company only records cash receipts and expenditures simply in a daily journal.